Emery, Louise (audio interview #2 of 4) - Emery, Louise (b. 1/00/1897 - d. 3/1/1985); Shirey, Robin, interviewer
INTERVIEW DESCRIPTION - This second interview with Louise Emery, which covers her early work experiences and her position at the First Congregational Church in Los Angeles, was conducted in her living quarters at Pilgrim's Place. The audio quality of the interview is good. 2/10/1977